Uluslararası işletmelerde kriz yönetimi, krizde uygulanan işletme stratejileri ve bir uygulama - Kahraman, Mehmet (My University, 2001)
International firms are comfronted with various enviroment factors because of newly developing events.These factors in drive the firm from normal situation to cirisis enviroment. In this situation, companies are obliged to benefit it from a new management style. This style is crisis management. Crisis management has got different features from normal activities. Firms cannot get mid off crisis situations using oldmanagement techniques. Crisis management is a short time activity, that draws the lines at firms life time . Crisis management involves three steps ;before crisis a during crisis and after crisis. İmportant subject in management of crisis before it happens .The most important thing in crisis management is to make studies that will help to realize the accoruence of crisis plans, that will guide the enterprise during the crisis, must be propored before it happens. This program must especially include the strategies and applications that should be realized by the enterprise, at the time when the crisis happens. Although, crisis and strategy concepts are to be perceived negatively by the managers, they are two terms which should be considered with each other. As international business managers don't study crisis and crisis strategy, they won't be able to benefit from the oppornuties and advantage of it. Management levels will behave negatively or pasitively to crisis management and strategy stduies according to their own opinions. As soon as the crisis management and business strategies are used together, crisis will be unavoidable enterprise strategy to play in global arena and in complex enviroment nternational Business , Crisis, Crisis Management, Strategy, Crisis in Strategy
Keywords: Genel yönetim; İŞLETME; KRİZ YÖNETİMİ; ULUSLARARASI Şirketler